Developing social indicators for farming social life cycle assessment in North Sumatra. - Dany Juhandi; Tri Martini; Nilam Kemala Odang; Widya Dara Anindya (Agriekonomika, 2026)
The social sustainability impact of the Food Estate Program has been the subject of extensive research, providing an evaluation assessment of social, economic, and environmental aspects. However, there has been a paucity of research examining the farmers surrounding the Food Estate Program in greater detail, especially regarding its social impacts. The present study employs the Social Life Cycle Assessment (S-LCA) to analyze the social impacts. The S-LCA is a methodological approach that utilizes primary data from various stakeholders, including farmers, governments, farmer groups, and the broader community. The objective of this study is threefold: first, to ascertain the social criteria employed to evaluate the social impact of strategic commodity farming; second, to examine the experiences and expectations of stakeholders concerning farming activities from a social perspective; and third, to identify the aspects of social sustainability in strategic commodity farming. The findings indicate that the social impact category that exerts the most significant influence on agricultural practices is that of socio-economic factors. Of the five social impact categories, only human rights and socio-economics demonstrate conditions that surpass the expected range. To achieve social sustainability, stakeholders in the strategic commodity farming system must collaborate to establish effective governance.